Hubungan Beban Kerja dengan Stres Kerja Karyawan Operator Produksi Pada PT X - Saputra, Farhan; Adetya, Sandra (Jurnal Ilmiah Wahana Pendidikan, 2026)
The study aimed to examine the relationship between workload and work stress among production operators at PT X. The research employed a quantitative correlational method using total sampling with 114 respondents. The workload was measured using the NASA-TLX scale base on hart staveland, while work stress was assessed using dimensions from Robbins. Validity and reliability test indicated that both instruments were highly reliable (α = 0.973 and α = 0.974). Data analysis using Pearson correlation revealed a positive and significant relationship between workload and work stress (r = 0,882, p < 0.0001), indicating that higher workload is associated with higher levels of stress. Most employees experienced high workload (91.23%) and high work stress (65.79%). These findings emphasize the need for effective workload management and stress reduction strategies in the workplace. The study suggest that companies should evaluate workload regularly and provide psychological support programs for employees.